The evolution of bicontinuous polymeric nanospheres in aqueous solution. Issue 18 (8th April 2016) - McKenzie, B. E.; de Visser, J. F.; Portale, G.; Hermida-Merino, D.; Friedrich, H.; Bomans, P. H. H.; Bras, W.; Monaghan, O. R.; Holder, S. J.; Sommerdijk, N. A. J. M.
Abstract : Complex polymeric nanospheres in aqueous solution are desirable for their promising potential in encapsulation and templating applications. Abstract : Complex polymeric nanospheres in aqueous solution are desirable for their promising potential in encapsulation and templating applications. Understanding how they evolve in solution enables better control of the final structures. By unifying insights from cryoTEM and small angle X-ray scattering (SAXS), we present a mechanism for the development of bicontinuous polymeric nanospheres (BPNs) in aqueous solution from a semi-crystalline comb-like block copolymer that possesses temperature-responsive functionality. During the initial stages of water addition to THF solutions of the copolymer the aggregates are predominantly vesicles; but above a water content of 53% irregular aggregates of phase separated material appear, often microns in diameter and of indeterminate shape. We also observe a cononsolvency regime for the copolymer in THF–water mixtures from 22 to 36%. The structured large aggregates gradually decrease in size throughout dialysis, and the BPNs only appear upon cooling the fully aqueous dispersions from 35 °C to 5 °C. Thus, the final BPNs are ultimately the result of a reversible temperature-induced morphological transition.